Application of ancient DNA methodologies to forensic science - Mouttham, Nathalie (My University, 2015)
Forensic scientists and ancient DNA researchers face similar challenges with respect to genetic information acquisition and analysis. However, these communities differ in one critical aspect: while forensic science is regulated by the strict guidelines of the judicial community, ancient DNA is a research-based academic field free to explore emerging technologies as they arise. This thesis investigates the application of two methodologies, developed in ancient DNA research, to challenging extracts, in hopes of modernizing forensic models while maintaining compatibility with current standards. The first chapter focuses on blunt-end sequencing library preparation protocols previously optimized for ancient DNA specimens. Forensically-relevant extracts were converted into libraries and typed by short tandem repeats (STR) amplification. When compared to STR profiles from pre-library extracts, a significant decrease in the quality was observed, in the form of allelic drop-out, heterozygous peak imbalance and increased stutter ratios. The second chapter discusses the efficacy of two enzymatic DNA repair methods, “PreCR® Repair” and “Nelson”, on typical ancient DNA specimens. Based on endogenous sample content, fragment length variation and base misincorporation rates, some DNA repair was reported when using PreCR®. However, the use of the Nelson protocol is not recommended for use in its current state. Both sequencing library preparation and enzymatic DNA repair show potential application to forensic evidential material, but require further analyses to confirm hypotheses and observations outlined in this thesis.
Keywords: Ancient DNA; Forensic science; High throughput sequencing; DNA repair